(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
the author tried to discuss and prove the formula of historical inversion and its structure while researching the works of different scholars. In the meanwhile, a number of narrative and structural techniques used to explore time shift phenomenon in the novel Cloud Atlas by David Mitchell.